Outbreak of Leptospirosis in Kerala - James, Sruthi; Sathian, Brijesh; Teijlingen, Edwin van; Asim, Mohammad (Nepal Journal of Epidemiology, 2018)
In South Asia, the monsoon brings life to vegetation, but at the same time has potential to cause public health problems. Notably, the climate change due to global warming is affecting the extent of monsoon rainfall in the region causing flooding which increases the risks of major disease outbreaks. Flooding and standing water after heavy rainfall increases the risk of vector-borne diseases such as dengue, malaria, plague, chikungunya, typhoid, cholera and Leptospirosis. Worldwide, Leptospirosis is one of the most common and emerging zoonoses, except on the North and South Poles. Rat fever or leptospirosis is a bacterial infection caused by the spiral-shaped bacteria (spirochete) of the genus Leptospira. This infection is mainly seen in wild and even domesticated species of rodents. It is mainly transmitted to humans by exposure of the mucous membranes (oral, nasal & eye) and skin abrasions or cuts to the urine or tissues of infected rodents or soil contaminated by their urine. Rats are the primary reservoir of leptospirosis, although farm animals and livestock, such as horses, pigs, dogs or cattle, and even wild animals can also be a reservoir for the bacteria. However, human-to-human transmission seems to occur occasionally. It is also an occupational hazard with potential risk of exposure among outdoors workers such as farmers, cleaners, veterinarians, agricultural workers. Moreover, there exists an increased chance of a recreational hazard to those who swims and wades in contaminated waters .